CREATIVITY, PROACTIVE PERSONALITY, AND ENTREPRENEURIAL INTENTION: THE ROLE OF ENTREPRENEURIAL ALERTNESS - Sean Lawrence; Patricia Patricia (Universitas Pelita Harapan, 2023)
Millions of people live in uncertainty even more after the COVID-19 pandemic. Therefore, creativity, proactive personality, entrepreneurial alertness, and entrepreneurial intention are required to reach the break-even point or gain business opportunities during the pandemic. This research aims to analyze the effects of university students' creativity and proactive personality towards entrepreneurial intention through a mediating role of entrepreneurial alertness in Indonesia. The research is quantitative and it uses non-probability sampling. The respondents for this study are 370 university students in Indonesia. The data was gathered using an online questionnaire and tested using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 4.0 by conducting validity, reliability, and hypothesis tests. Based on the hypothesis testing, the research shows that creativity has a positive effect on entrepreneurial alertness, proactive personality has a positive effect on entrepreneurial alertness, entrepreneurial alertness has a positive effect towards entrepreneurial intention, creativity has a positive effect towards entrepreneurial intention through a mediating role of entrepreneurial alertness, and proactive personality has a positive effect towards entrepreneurial intention through a mediating role of entrepreneurial alertness.